Lactobionic Acid-Navigated Gold Nanorods With Light-Triggered “on-Demand” Drug Release for Synergistic Photothermal-Chemotherapy - Zhang, Zhang; Sun, Chunyang (Frontiers in Materials, 2022)
The rational design of the nanocarriers with active tumor targeting and specific chemotherapy for heat shock protein 90 (Hsp90) inhibition is attractive for combined chemo-photothermal therapy (PTT). Herein, a smart gold nanorod (GNR)-cored micelle (T-GNRAAG) was developed to encapsulate 17-allylamino-17-demethoxygeldanamycin (17-AAG, Hsp90 inhibitor) through a facile preparation approach. The characteristics of T-GNRAAG were evaluated both in vitro and in vivo. The designed nanoplatform possessed sufficient 17-AAG loading content and lactobionic acid-mediated active targeting for hepatoma cells. More importantly, the 808 nm laser irradiation not only initiated PTT for cell killing, but also remotely triggered 17-AAG liberation within cancer cells via inducing phase transition of poly(ɛ-caprolactone). All these features forcefully supported the effectiveness of T-GNRAAG in tumor growth inhibition. This work represents a proof-of-concept combinatorial chemo-PTT treatment.